IR and Uv-Visible Study of the Thermal Stabilization for pvc Stabilized with ( Ho,Tb and Dy ) Stearate and Synergistic Mixtures - Al-Huseini, H. A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Three types of metal carboxylates (Ho,Tb and Dy) stearates were LLSed as thennal stabi lizers for PVC. Infrared spectra (1500-1900 ) cm.1 were studied for PVC films stabilized with these metal carboxylatcs. Two types of oxygen were round -containing products that were formed during the thermal degradation .On the other hand , the presence of atmospheric oxygen leading to the formation of carbonyl groups on the chain seems to play a great role in the stabilization of PVC.It was found that IR spectroscopy was suitable to follow the consumption of the carboxylatcs within the thermal stress periods via antisymmetrical stretching vi bration of COO. The thermal stability ior the PVC in present of synergistic mixtures (Ho-Tb,Ho-Dy and Tb-Dy) stemÂ·ates was studied by U l traviolet-visi ble spectra.The results indicate that these mixtures have considerable stabilization efficiency for the PVC.